Permanent health education to qualify the reception of women victims of violence: debating a proposal (Research, Society and Development, 2020)
This article aims to present a proposal for intervention, within the scope of work management and health education, to qualify the reception to women victims of domestic violence. This is an action research with qualitative approach, developed in the context of the coverage area of the Basic Health Unit (UBS) Parque Ludolf, located in the municipality of Mesquita/RJ. The methodological route was composed of three phases: exploration, planning and execution. The proposed intervention is an educational action for health workers, developed in the light of the principles and guidelines of the National Policy of Permanent Education in Health. With this intervention, it is expected that workers at UBS Parque Ludolf can have a better view. humanized to accommodate a victim of domestic violence. Moreover, that skilled workers are knowledge multipliers, in order to contribute to the reduction of the number of cases of violence against women and the professional qualification of other health workers in Mesquita. This proposal, through continuing education, could foster a more qualified approach to women's health, with an emphasis on caring for women victims of violence.